1996
DOI: 10.1212/wnl.47.5.1329
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and tolerability of recombinant human ciliary neurotrophic factor in patients with amyotrophic lateral sclerosis

Abstract: We examined the toxicity of both single and multiple subcutaneous injections of recombinant human ciliary neurotrophic factor (rhCNTF) in 72 patients with ALS, in doses ranging from 2 to 100 micrograms/kg. Adverse events were generally dose related and ranged from mild to severe. The tolerability of daily subcutaneous rhCNTF was equivalent to placebo at doses < or = 5 micrograms/kg/day. At higher doses, anorexia, weight loss, reactivation of herpes simplex virus (HSV1) labialis/stomatitis, cough, and increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 4 publications
2
53
0
Order By: Relevance
“…Indeed, we observed a reduction in weight gain and a dilatation of the left cardiac ventricle in AdCT-1-treated animals. Weight loss, proinflammatory responses, and induction of acute-phase proteins can be caused by several cytokines and have been extensively described after CNTF injection (21,(50)(51)(52). The stigmates of dilated cardiopathies that we observed in AdCT-1-treated normal mice are consistent with the morphological changes of cardiomyocytes cultured in the presence of CT-1 (53) and support the assumption that the neuroprotective effects of CT-1 in pmn mice might have been counterbalanced by its systemic toxicity.…”
Section: Figuresupporting
confidence: 85%
“…Indeed, we observed a reduction in weight gain and a dilatation of the left cardiac ventricle in AdCT-1-treated animals. Weight loss, proinflammatory responses, and induction of acute-phase proteins can be caused by several cytokines and have been extensively described after CNTF injection (21,(50)(51)(52). The stigmates of dilated cardiopathies that we observed in AdCT-1-treated normal mice are consistent with the morphological changes of cardiomyocytes cultured in the presence of CT-1 (53) and support the assumption that the neuroprotective effects of CT-1 in pmn mice might have been counterbalanced by its systemic toxicity.…”
Section: Figuresupporting
confidence: 85%
“…However, other studies suggest that CNTF can affect muscle excitation and reverse insulin resistance, and when used in muscle cultures CNTF regulates stem cell differentiation and protein synthesis, suggesting numerous mechanisms through which the ageassociated decrease in CNTF identified here could contribute to sarcopenia (11,45,63,65). Given these findings together with genetic studies showing that variations of CNTF and its receptor influence muscle strength and function (2,13,14,51) and that CNTF is being used in clinical trials for neurodegenerative disease (20,41), it is surprising that CNTF expression in human skeletal muscle has not been extensively quantified. Unfortunately, side-effects of weight loss and anorexia seen in the trial for treatment of neurodegeneration led to CNTF being tested in obesity.…”
Section: Discussionmentioning
confidence: 62%
“…50 So far, side effects of CNTF such as fever, malaise, and weight loss as well as the most likely poor ability of CNTF to cross the intact BBB have limited the success of clinical studies in amyotrophic lateral sclerosis patients who were given CNTF because of its known neuroprotective effect. 28,31,32 More promising results were obtained when CNTF was administered to the CNS by intrathecal injections or implantation of encapsulated transfected cells into the ventricular system. 34,36,37,81,82 Recent progress on human CNTF biochemistry indicated that this cytokine can use soluble or membrane-bound IL-6R␣ as a substitute to CNTFR␣ to activate the receptor signaling subunits, gp130 and LIFR␀.…”
Section: Discussionmentioning
confidence: 99%
“…28 -30 CNTF was administered systemically to patients with amyotrophic lateral sclerosis, but no beneficial effect was detected. 28,31,32 The lack of therapeutic efficiency could be linked to the poor ability of CNTF to pass the bloodbrain barrier (BBB). 33 More promising preclinical or clinical results have been obtained with CNTF targeted to the CNS by intrathecal injection or implantation of encapsulated transfected cells.…”
mentioning
confidence: 99%